Eine magische Gemme mit Inschriften im Akademischen Kunstmuseum der Universität Bonn - Zwierlein-Diehl, Erika (Acta Classica Universitatis Scientiarum Debreceniensis, 2024)
The magical gem published here belongs to the Akademisches Kunstmuseum der Universität Bonn (Abb. 1–2.; measurements: 33 x 24 x 6 mm). It stems from the collection of Klaus Müller, who acquired it in the 1960th or 1970th. Obverse and reverse of the gem are filled with inscriptions, most of them consisting of unknown voces magicae, and possibly some meaningless letters to fill the space. On the obverse a prominent inscription invokes Eloe, that is Elohim, the Jewish God, who entered the magic pantheon like Greek and Egyptian ones and under the name of Iaō, even got an image in the figure of the cock-headed, snake-legged warrior. Eloe here means the great magic Sun god, as becomes apparent by Semese(ilam) in col. d 6. The reverse names Thoth, the Moon god. Thus the gem was an amulet for day and night, that is for ever. The bevel of the gem is left plain, so it could have been personalizied by an inscription, which was not the case; thus in its present form the gem was an amulet for every owner.